Understanding the role of low glass transition temperature excipients in the mitigation of amorphisation on mechanical processing - GALLAGHER, KIERAN HUBERT (Trinity College Dublin. School of Pharmacy & Pharma. Sciences. Discipline of Pharmacy, 2017)
Commonly employed pharmaceutical processes such as milling, blending and compaction may unintentionally lead to the generation of amorphous regions or metastable polymorphic forms in crystalline active pharmaceutical ingredients (APIs). An important characteristic of the API with regard its propensity to amorphise on processing is its glass transition temperature (Tg), with higher Tg materials generally exhibiting a greater amorphising tendency. We investigated the ability of various low Tg crystalline excipients to mitigate process induced amorphisation of three model high Tg APIs, with a focus on gaining mechanistic insights into the phenomenon. The low Tg dicarboxylic acids, succinic acid (SA), glutaric acid (GA), adipic acid (AA) and pimelic acid (PA), in addition to the low Tg polyol mannitol (MAN) were co-processed with the high Tg APIs - budesonide (BD), sulfadimidine (SDM) and acyclovir (ACV). Milling studies were performed in a planetary ball mill (PBM) at room temperature (RT) and at 4?C and in a vibratory ball mill (VBM) at both RT and cryo-temperature (CT). Compaction studies were performed in a single punch tablet press while blending studies were performed in a tumbler mixer. GA was found to be the most successful excipient at mitigating amorphisation of BD on comilling at RT, which was consistent with previous studies. Both PA and AA exhibited partial abilities to mitigate amorphisation, while neither SA nor MAN were successful in this regard. None of the excipients were able to effect mitigation of amorphisation on comilling at CT. The relative abilities of the excipients to drive Tg reduction of the high Tg APIs on comilling broadly correlated with their respective abilities to mitigate amorphisation. In particular, both SA and AA were unable to reduce the Tg of either SDM or BD on comilling to the same extent as either GA or PA. The formation of hydrogen bonding interactions between amorphous API and the excipients on comilling was assessed. Phase separation studies from the amorphous API: excipient composites suggested that crystallisation was driven by the low Tg excipient with concomitant crystallisation of both API and excipient, highlighting the importance of hydrogen bonding in driving the crystallisation of the API. In contrast, neither evidence for hydrogen bonding interactions, Tg reduction or mitigation of amorphisation was observed on co-blending or co-compaction studies. The experimental solubility of excipient in amorphous API and the calculated Hildebrand solubility parameters were found to not be good predictors alone of the relative abilities of the diacids to mitigate amorphisation on comilling. While the inability of MAN to effect Tg reduction on comilling was attributed to immiscibility in the liquid/ glass solution state, the level of Tg reduction on comilling with the diacids was correlated with the solid-state properties of their crystalline forms. We considered our results in the context of the driven materials theory which accounts for the phase transformations of crystalline materials to high energy amorphous states, utilising the concept of the effective temperature on milling. Similarly, the paradoxical ability of a mechanical driving force to drive crystallisation of the API from the reduced Tg composites (thereby mitigating amorphisation) was also considered in the context of the effective temperature concept introduced in non-equilibrium physics.
APPROVED